The olfactory limbus of the red fox (Vulpes vulpes). New insights regarding a noncanonical olfactory bulb pathway - Ortiz-Leal, Irene; Torres, Mateo V.; Vargas-Barroso, Víctor; Fidalgo, Luis Eusebio; López-Beceiro, Ana María; Larriva-Sahd, Jorge A.; Sánchez-Quinteiro, Pablo (Frontiers in Neuroanatomy, 2023)
Introduction: The olfactory system in most mammals is divided into several subsystems based on the anatomical locations of the neuroreceptor cells involved and the receptor families that are expressed. In addition to the main olfactory system and the vomeronasal system, a range of olfactory subsystems converge onto the transition zone located between the main olfactory bulb (MOB) and the accessory olfactory bulb (AOB), which has been termed the olfactory limbus (OL). The OL contains specialized glomeruli that receive noncanonical sensory afferences and which interact with the MOB and AOB. Little is known regarding the olfactory subsystems of mammals other than laboratory rodents. Methods: We have focused on characterizing the OL in the red fox by performing general and specific histological stainings on serial sections, using both single and double immunohistochemical and lectin-histochemical labeling techniques. Results: As a result, we have been able to determine that the OL of the red fox (Vulpes vulpes) displays an uncommonly high degree of development and complexity. Discussion: This makes this species a novel mammalian model, the study of which could improve our understanding of the noncanonical pathways involved in the processing of chemosensory cues.